أثر آليات حوكمة الشركات على الأداء المالي للمصارف: دراسة تطبيقية على عينة من البنوك الجزائرية - بن عيسى, ريم (جامعة الوادي - University of Eloued, 2017)
نظرا لما تشهده المصارف من تنوع وتعقد وما تتسم به من مخاطر كبرى فقد أصبح وجود نظام حوكمة المصارف عن طريق تطبيق وتفعيل آليات تساهم في الحد من الفساد ضرورة حتمية لتأكيد حسن اداء الصناعة المصرفية حول العالم. وهدفت هذه الدراسة الى ابراز تأثير آليات حوكمة المصارف على الأداء المالي للبنوك الجزائرية في الفترة (2011-2015) من خلال قياس درجة تطبيق البنوك محل الدراسة لآليات حوكمة المصارف بإستخدام برنامج spss وبعدها تقييم الأداء المالي لعينة الدراسة بإستخدام مجموعة من المؤشرات due to the diversity and complexity of the banks, and the great risks they face. The existence of the banking governance system through the application and activation of mechanisms that contribute to reducing corruption is imperative to the improve of the banking industry around the world. This study aims to highlight the impact of banking governance mechanisms on the financial performance of the Algerian banks from (2011 to 2015). And this will by measuring degree applying banking governance mechanisms or not by using the spss program. Then performance financial assess by using a set of indicators.
The impact of corporate governance mechanisms on bank performance financial A applying study of a sample a banks Algerian
مقال بمجلة الدراسات المالية والمحاسبية . مج 08 ع01. جوان 2017 . جامعة الوادي
Keywords: حوكمة المصارف، آليات حوكمة الصارف، الأداء المصرفي; banking governance, banking governance mechanisms ,banking performance